Tai Dam: Cultural dynamics and the maintenance of ethnic identity through music - จันทร์ศรี, สุธี; บุรุษพัฒน์, สมทรง (Journal of Language and Culture, 2018)
This paper aims to explain the identity maintenance of the Tai Dam ethnic group through an analysis of musical components found in the musical culture of the ethnic group within three socio-cultural contexts in three countries: Vietnam, Laos, and Thailand. This study was conducted through the integration of cultural and musical anthropological methodology. The results reveal unique differences in Tai Dam musical culture between each country that reflect a diverse ethnic identity maintenance process within different contexts. They include: 1) a fortification of ethnic awareness process in the form of reproduction of ethnic ideology by means of unique musical attributes known only to ethnic group members; 2) the selection of unique musical attributes for demonstration in order to make the Tai Dam culturally-distinct from other ethnic groups; 3) modernized Tai Dam music created by blending traditional with contemporary music to reveal its adaptability and assert its value as equal to that of value that is not inferior to modern music; and 4) the adaption of conventional musical components which are transferred to the members of the ethnic group thereby redefining the heritage that reflects their cultural and ethnic identity. These changes indicate that, notwithstanding the diminishing role of traditional musical culture in ethnic society, the Tai Dam ethnic group has been able to learn about and create distinguishing music in an attempt to exploit it as a cultural symbol that leads to the maintenance of their ethnic identity within an ever-changing cultural dynamism.